Characteristics of Pigs Farming System in The Bruyadori District Biak Numfor Regency - Antomina Estefina Koibur; Denny Iyai; John Arnold Palulungan (Bantara Journal of Animal Science, 2019)
Bruyadori District Biak Numfor Regency is one of areas that supply pigs to several regions in Papua. One of the regions supplied is Nabire Regency. Pigs have a high economic value in Papuan society, because pigs can be used as savings, are very useful in customs events in Papua (paying fines, dowry) and demand for pork increases at ecclesiastical events (Christmas and Easter). This research is expected to provide an overview of the characteristics of pig farming systems in Bruyadori District, Biak Numfor District. The research method used is descriptive research method with case study techniques, the case in this study was farmers. There were 30 respondents who were taken to get data. Pig farmers in Bruyadori District are 100% Biak or Papuan indigenous tribes, and judging from their education background, it is still very low mostly only have elementary and junior high school diploma but the experience of breeding is very good, about 20 - 40 years, whereas the purpose of raising livestock as a side business, farmers have a main job as farmers and fishermen so the number of livestock ownership is still less than 1-5 pigs because the number of livestock is influenced by the number of litter size and farowing rate which is very low every year, about 1-5 pigs and the number of sow that is productive is only 1 sow. Farmers in the Bruyadori District provide feed still from the garden and household waste or food scraps from the kitchen. The maintenance system applied is an extensive and intensive maintenance system.Keywords: Bruyadori District, Biak Tribe, Pigs, Maintenance System